PENTINGNYA IMPLEMENTASI NILAI PANCASILA SILA KESATU DALAM MENUMBUHKAN KARAKTER SISWA SEKOLAH DASAR – ANALISIS STUDI PUSTAKA - Diana Aliansyah Sopia; Mayang Avrilla; Robi Anawiyah Sya’bani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The application of Pancasila values ​​is very important in developing the character of elementary school students in everyday life. The application of the values ​​in the first precepts of Pancasila is based on "Belief in the One and Only God". The purpose of this study was to find out how the implementation of Pancasila values ​​in the first precepts among elementary school students. The research method used was literature study with 15 journal articles reviewed. The results show that the application of the first Pancasila values ​​is very important in growing the character of elementary school students. Where the character can be formed in a short time. The role of parents and teachers is very influential in the implementation of the implementation of Pancasila values, especially the first precepts in students' daily lives.